Peranan Kepemimpinan Transformasional Dalam Memoderasi Pengaruh Kompetensi Dan Beban Kerja Terhadap Kinerja Polisi Kehutanan - Hendri Dunan; Evi Susanti Tasri (CV. ITTC INDONESIA, 2022)
The Forest Police is one of the regional technical implementing units of the Forestry Service of West Sumatra Province. So it becomes interesting to examine the performance of these employees. This study aims to analyze the performance that is influenced by the variables of competence and work and the moderating role of transformational leadership. The results of this study state that partially there is a significant influence between competence and a positive and significant effect on performance, workload has a negative and insignificant effect on performance, transformational leadership has a positive and significant effect on performance, transformational leadership moderates competence and performance and has a positive and significant effect on performance. not significant and transformational leadership moderates workload with performance and has an insignificant effect.